Fabrication and applications of van der Waals heterostructures. (1st June 2023) - Qi, Junlei; Wu, Zongxiao; Wang, Wenbin; Bao, Kai; Wang, Lingzhi; Wu, Jingkun; Ke, Chengxuan; Xu, Yue; He, Qiyuan
Highlights: The major synthetic strategies of van der Waals heterostructures based on 2D materials are introduced, including physical combination, gas-phase deposition, solvothermal synthesis and synchronous evolution. The fundamental principles, development trends, and strengths/weaknesses of each synthetic strategy are elaborated. The integration strategies of van der Waals heterostructures and their preferred applications are discussed, including electronics, photodetectors and energy-related applications. The potentials and challenges arising in the van der Waals heterostructures synthesis and applications are envisioned. Abstract: Van der Waals heterostructures (vdWHs) are showing considerable potential in both fundamental exploration and practical applications. Built upon the synthetic successes of (two-dimensional) 2D materials, several synthetic strategies of vdWHs have been developed, allowing the convenient fabrication of diverse vdWHs with decent controllability, quality, and scalability. This review first summarizes the current state of the art in synthetic strategies of vdWHs, including physical combination, deposition, solvothermal synthesis, and synchronous evolution. Then three major applications and their representative vdWH devices have been reviewed, including electronics (tunneling field effect transistors and 2D contact), optoelectronics (photodetector), and energy conversion (electrocatalysts and metal ion batteries), to unveil the potentials of vdWHs in practical applications and provide the general design principles of functional vdWHs for different applications. Besides, moiré superlattices based on vdWHs are discussed to showcase the importance of vdWHs as a platform for novel condensed matter physics. Finally, the crucial challenges towards ideal vdWHs with high performance are discussed, and the outlook for future development is presented. By the systematical integration of synthetic strategies and applications, we hope this review can further light up the rational designs of vdWHs for emerging applications.